Menurunkan angka rework pada proses burritori di line injection moulding dengan metode PDCA - Selamet Riadi; Shiro Esa Emerzet; Dani Prasetyo (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
Case heater & case blower is one of component product used to make car air conditioner. The function of case heater & case blower is as a holder for various car A/C components. Case heater & case blower is produced with a mould with the support of plastic injection machine. The process is to inject the material melt into the mould. When the product comes out of the machine, it checks the product to remove the burr on the product. Burr is a minor type of defect in the product, meaning the product can still be said OK but an additional process should be done to clean the product. Additional process is called burritori, which is a process to clean burr by using cutter. Allowed burr standard of 0.1 ~ 0.3 mm, above it must be done burritori process. With the company's slogan of QUALITY FIRST, the quality of product is very important. Therefore the burritory process can not be eliminated. With the burritory process, so have additional man power to do that activity. Actually unneeded additional man power to do burritori process if product out of mould in good condition that there is no burr on product. This study aims to improve product quality by addressing the product burr problem after being out of mold. So with the increased product quality that is the absence of burr, then the burritory process previously done no longer need to be done because the product comes out of the mold already good quality (no burr). In this research using PDCA method in solving existing problems.